Occupational physical activity differentially affects the risk for developing later-onset Crohn's disease and ulcerative colitis among middle-aged and older populations. (1st February 2022) - Furuya, Yuko; Fukai, Kota; Nakazawa, Shoko; Kojimahara, Noriko; Hoshi, Keika; Toyota, Akihiro; Tatemichi, Masayuki
Abstract: Background: A person's occupation may increase his/her risk for developing inflammatory bowel disease (IBD). This study investigated the association between risk for later-onset of IBD and both specific occupations and occupational physical activity (OPA) levels. Materials and methods: A multicenter hospital-based matched case-control study was conducted using the Inpatient Clinico-Occupational Survey database. Cases were patients with Crohn's disease (CD) and ulcerative colitis (UC) patients admitted for the first time between 2005 and 2015. Four controls matched by age, sex, admission year and hospital were selected for each case. Cases and controls were grouped into the longest-held occupations as classified by the Japanese Standard Occupational Classification and OPA levels. We conducted conditional logistic regressions to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for IBD, CD and UC adjusted for alcohol consumption and smoking status. Results: There were 564 cases (172 CD, 392 UC) and 2086 controls. The risk for UC was higher among sales workers and carrying, cleaning and packing workers (ORs 2.62 [95%CIs 1.18–5.82], 2.52 [1.04–6.09]). There was no association between occupation type and CD risk. Higher OPA level decreased CD risk (OR 0.51 [95%CIs 0.26–1.00]) and increased UC risk (OR 1.53 [95%CIs 1.02–2.30]). Conclusions: Our study revealed that the risk for later-onset of UC, but not CD, was associated with longest-held 'service' and 'manufacture' work. The risk by OPA levels was inversely associated between CD and UC. Further studies are needed by follow-up method for long-term effects of physical activity.